Collaborative Governance in Digital Licensing Services in Batam - Rusmawati Rusmawati; Iranda Firiansyah (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study examines the implementation of collaborative governance in digital licensing services in Batam, a strategic investment hub and Free Trade Zone characterized by complex institutional arrangements. The research aims to analyze how collaborative governance mechanisms contribute to the effectiveness of digital licensing services and to identify factors that facilitate or constrain stakeholder collaboration. A qualitative case study approach was employed, utilizing semi-structured interviews, observations, and document analysis. Data were analyzed using thematic analysis based on the collaborative governance framework, which includes face-to-face dialogue, trust building, commitment to the collaborative process, shared understanding, and intermediate outcomes. The findings indicate that collaborative governance plays a crucial role in supporting digital licensing services by strengthening communication, fostering trust among stakeholders, improving institutional coordination, and facilitating joint problem-solving. Although challenges related to data integration, regulatory synchronization, and organizational capacity remain, collaborative practices have contributed to greater service efficiency, transparency, and accessibility. The study concludes that successful digital licensing services depend not only on technological innovation but also on effective collaboration among stakeholders, highlighting the importance of collaborative governance as a foundation for sustainable digital public service delivery.